Integrating Mind-Mapping Collaborated with Think-Pair-Share to Teach Reading Comprehension in Descriptive Text - Catur Kepirianto; Siti Mariam; M. Ulya Ashari (Master Program in Linguistics, Diponegoro University, 2022)
The study aims at explaining the effectiveness of integrating Mind-Mapping collaborated with Think-Pair-Share to teach reading comprehension in descriptive text. It employed quantitative method using control-group of non-equivalent of quasi experimental research design. The study was conducted at eighth graders of a private junior high school in Batang, Indonesia. The research procedure used pretest, post-test, and documentation. Data analysis technique applied t-test formula SPSS 25 version program. The finding shows that experimental class taught by Mind-Mapping collaborated with Think-Pair-Share has higher achievement in posttest than control class taught by traditional method. The mean post-test of experimental class, 85.00 is higher than that of control class namely 49.50. The conclusion infers that Mind-Mapping collaborated with Think Pair Share is effective to teach reading in descriptive text. It can be recommended to English teachers for using this learning model in EFL classroom in order to create meaningful and joyful learning.